Research on Deep Learning-Based Algorithm and Model for Personalized Recommendation of Resources - Liu, Yu’e (Bright Publisher, 2023)
Resource recommendation system is a new type of management system, which uses personalized information to solve business needs such as customer consultation and product recommendation, and provides users with high quality services and achieves accurate marketing, so nowadays resource recommendation system has a pivotal role in modern resource management. In this paper, I study the algorithm and model of resource personalized recommendation based on deep learning, taking human resource recommendation as an example.